Analysis of a novel concept of 2-stroke rod-less opposed pistons engine (2S-ROPE): Testing, modelling, and forward potential. (15th January 2021) - Serrano, J.R.; Arnau, F.J.; Bares, P.; Gomez-Vilanova, A.; Garrido-Requena, J.; Luna-Blanca, M.J.; Contreras-Anguita, F.J.
Graphical abstract: Highlights: A new 2 S opposed pistons engine architecture has been designed and assembled. The engine is conceived for automotive range extender of plug-in hybrid vehicles. Main engine attributes: simplicity, low-vibration and mechanical losses reduction. After the Experimental campaign a 1-D model was developed for forward studies. Port injection, direct injection and lean combustion strategies are assessed. Abstract: As pollutants and fuel consumption requirements become more constraining, new internal combustion engines generation arise to fulfill future automobile market regulations. In these context spark ignition (SI) engines working under hybridized structures are expected to represent one of the most viable and feasible technical approaches. In parallel to the already implemented 4-stroke turbocharged engines, new engine concepts are being conceived from their birth to meet nowadays standards. This work shows a new engine concept assessed to fit series hybrid configurations from the earliest design stages, and to fulfil requirements of the named "zero-emissions" urban areas. In this research work, a new opposed piston 2-stroke engine architecture based on rod-less innovative kinematics is described. The potential of this engine is based on its compactness, absence of vibrations and simplicity, going in hand with very competitive figures in terms of power density and fuel consumption. The engine unit has been designed, assembled, and tested to analyze several performance aspects, such as gas exchange and combustion. Taking advantage of the experimental campaign, a one-dimensional (1D) gas-dynamics engine model was developed and validated. Finally, the engine model was used for analyzing several potential upgrades and results have been discussed in detail. The target has always been to improve fuel consumption figures, below the best standards in market available internal combustion engines, while keeping engine concept simplicity and building costs.